Susceptibilidade antimicrobiana de Escherichia Coli isoladas de aves abatidas sob inspeção no estado do Tocantins - Nepomuceno, Leandro Lopes (Universidade Federal do Tocantins, 2016)
The Escherichia coli (E. coli) have been widely studied being a scattered agent in the environment considered a causative microorganism of disease in both men as in animals, representing a major threat to public health, especially the high antibiotic resistance index. This study aimed to evaluate the antimicrobial susceptibility profile stems of E. coli isolated from viscera and the upper airway tract of poultry convicted under inspection in Tocantins state. The poultry were coming from the states of Goiás (GO), São Paulo (SP), Tocantins (TO) and the Distrito Federal (DF). The results showed that among the antibiotics tested, six were indicated for treatment of Escherichia coli in chickens, Ceftioflur, Florfenicol, Ciprofloxacin, Trimethoprim + Sulfamethoxazole, Gentamicin, Amoxicillin + Clavulanic acid. The resistance to antimicrobials in strains percentage analyzed warn of a risk factor highlighting its importance and consequence for public health. It was observed that most of the samples showed resistance to groups of beta-lactam producers (43%), sulfonamides (39%) and tetracycline (47%), suggesting the character of multidrug resistance of the samples. From the data presented in this study, the use of antibiotics has not yet become a problem within the poultry industry in these states since the antibiotics tested were mostly effective on E. coli. However, we should not close the eyes to this situation since the microbial resistance profile is mutable in this way is important periodic studies on antimicrobial pattern of Escherichia coli in the regions of interest, since the susceptibility can vary from antibiotics pressure used.